PERAN KELOMPOK MASYARAKAT â€PANTAI NUNSUIâ€ DALAM KEBERLANJUTAN PENGELOLAAN WILAYAH PESISIR TAMAN WISATA ALAM LAUT (TWAL) TELUK KUPANG - Lebrina Ivantry Boikh; Jhon Septin Mourisdo Siregar; Maharani (TECHNO-FISH, 2023)
In managing the TWAL of Kupang Bay, synergy and participation of the surrounding community are needed to maintain and preserve the existing coastal and marine resources. The presence of the